Evaluation of the Potential Nephroprotective and Antimicrobial Effect of Camellia sinensis Leaves versus Hibiscus sabdariffa (In Vivo and In Vitro Studies) - Doa’a Anwar Ibrahim; Rowida Noman Albadani (Advances in Pharmacological Sciences)
Green tea and hibiscus are widely consumed as traditional beverages in Yemen and some regional countries. They are relatively cheap and the belief is that they improve health state and cure many diseases. The aim of this study was to evaluate the potential protective and antibacterial activity of these two famous plants in vitro through measuring their antibacterial activity and in vivo through measuring nonenzymatic kidney markers dysfunction after induction of nephrotoxicity by gentamicin. Gram positive bacteria like MRSA (methicillin resistant Staphylococcus aureus) were isolated from hospitalized patients’ different sources (pus and wound) and Gram negative bacteria including E. coli and P. aeruginosa were used in vitro study. In addition, the efficacy of these plants was assessed in vivo through measuring nonenzymatic kidney markers including S. creatinine and S. urea. Green tea was shown antimicrobial activity against MRSA with inhibition zone 19.67 ± 0.33 mm and MIC 1.25 ± 0.00 mg/mL compared with standard reference (vancomycin) 18.00 ± 0.00 mg/mL. Hibiscus did not exhibit a similar effect. Both Hibiscus- and green tea-treated groups had nephroprotective effects as they reduced the elevation in nonenzymatic kidney markers. We conclude that green tea has dual effects: antimicrobial and nephroprotective.